La Etnofarmacología y los Bioensayos como nuevas estrategias en la investigación fitoquímica de la flora medicinal peruana - Fuertes R., César M. (2001)
Since plants may contain hundreds or even thousands metabolites, the vegetable kingdom can be a posible source of new compounds for introduction into therapeutical screenning programmes. A realistic approach to this fascinating challenge is the development of the ethnopharmacology. In contrast to medicinal chemistry, ethnopharmacology can start from an observed activity of a drug used in man or animals. Subsequent bioassay-direct fractionation can lead to the discovery of previosly unknown chemical structures for further structure-activity studies. With automated sample injection and fraction collection, HPLC systems can readily and rapidly be used to isolale tens of milligrams of pure compound, whose structure is usually resolved by use of NMR spectroscopy. Finally, we have two strong recommendations to phytochemists entering this field: (i) Never launch a major project unless a sufficient supply of starting material is guaranteed, be it a plant or a locally used drug, (ii) An adequate bioassay should be found or developed for monitoring the isolation of active constituents. However, many of the groups working on natural products are base in universities and research institutes throughout Perú, are not very familiar with or well adapted to the new trends in drug discovery. Our hope that this paper will attract the attention not only the bioscientific community but the government because if the current trend of destruction of Amazon's habitats continues at its presente rate, phytochemist may have only a few chance to discover biomolecules for the human being and animal specimens.